Simulação numérica do escoamento de uma gota de óleo em água através de capilares com gargantas - Fejoli, Rômulo Fieni (2016)
This study is responsible for analyze the oil drop interfacial dynamics in water, which flows through a straight capillary and straight capillary with throat, both with axial geometry. The two-dimensional, transient, incompressible newtonian fluids, biphasic problem with small inertial forces, represents with a simplified form what happens in oil reservoir on the microscopic scale during the oil drops mobilization. The interface problem numerical solution is obtained by coupling the VOF (Volume of Fluid) and Level-Set methods. The results show that the dynamics of the motion process of the oil drop, mostly in capillaries with throat, result in reduced flow mobility, explained by the blocking factor parameter, being controlled by the dimensionless parameters: capillarity number, viscosity ratio and ratios of diameters (drop and capillary). It was obtained an interconnection between the parameters with the blocking factor, and its decay to values below one, with the viscosity ratio and the drop size rise and also a low sensitivity by reducing the number of capillarity. Overall, the oil drop deforms to a greater or lesser degree in response to the dimensionless parameters, showing a greater deformation with decreasing of the viscosity ratio and the number of capillarity. The presence of the throat significantly increases the pressure drop as well as the flow speed in the throat. All simulations were performed in the commercial software ANSYS® FLUENT® through a long learning process that allowed the acquisition of important knowledge to this work.